Reforma en la Ley Orgánica Electoral y de Organizaciones Políticas de la República del Ecuador, Código de la Democracia, Instituyendo las normativas para el caso de fallecimiento de los Alcaldes o Alcaldesas antes de su posesión legal - Chamba Pinta, Pedro Armando (2016)
This thesis entitled: "Reform of the Organic Law on Elections and Political Organizations of the Republic of Ecuador, Code of Democracy, instituting regulations for the case of death of Mayors before legal possession," his develop interest is due to hear a legal problem of legal vacuum in the Organic Law on Elections and Political Organizations of the Republic of Ecuador, Code of Democracy, which does not provide any legal provision that addresses and regulates to do in case of death Mayors from before its legal possession; because it is well known that once declared winner in the elections for the office of mayor the National Electoral Council or Provincial Electoral Board made the notification, however, lack the ceremony to meet as a possession in the month of May, as it provided by law, because once triumphant appropriated candidates or candidates in the elections, shall be considered completed the election process. In such circumstances it is feasible to further my study in order to propose alternative legal reform. The theoretical and field work of this thesis has allowed me to get criteria, with clear and precise grounds of well known literature, which contributed to the verification of targets, and testing of the hypothesis, allowing support reforms to the Organic Law on Elections and Policy of the Republic of Ecuador, Code of Democracy Organizations. 5 The content of this thesis is the result of an arduous legal research of the author in the scientific, legal, social and methodological level, which deals with theories and knowledge gained through scientific and statistical techniques and methods.